Electric Power Systems Research - Ying-Yi Hong (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
This book contains 21 research papers, one review and one editorial focusing on studies in the field of electric power systems research in 2016. These 23 published papers can be classified into five categories: generation systems; transmission systems; distribution systems; end-users; and the power market. Among these, the subjects of generation and distribution systems has caused the most concern due to the realization of smart grids. Papers presented in this book cover research, the development of new procedures or components, an original application of existing knowledge, or new design approaches. The authors of the published articles are from a variety of Asian, North American, and European countries. This book shows that authors in China are the most active and their research covers all of the above-mentioned areas.